2016
DOI: 10.15517/rbt.v64i3.21387
|View full text |Cite
|
Sign up to set email alerts
|

Captura y selectividad del zooplancton por Utricularia foliosa (Lentibulariaceae) en la Ciénaga de Paredes, Santander, Colombia

Abstract: Capture and selectivity of zooplankton by Utricularia foliosa (Lentibulariaceae) in the Ciénaga de Paredes, Santander, Colombia. Utricularia is a genus of carnivorous plants that capture a wide range of aquatic organisms. Most of these plants grow in environments with nutrients deficiency and have the ability to change the conditions of their microenvironment. The aim of this research was to study the selectivity in the zooplankton capture by Utricularia foliosa in the Ciénaga de Paredes. Our study was underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The pH and conductivity values recorded for the tropical lowland lakes in the study area were similar to those reported for other lowland lakes of the Middle Magdalena River, such as Ciénaga de Paredes, Ciénaga de Chucuri, Ciénaga de Aguas Negras, Ciénaga San Silvestre, Ciénaga del Opón, and Ciénaga Miramar (Pedraza et al, 1989;Ramírez & Viña, 1998;Pava et al, 2006;Barón-Rodríguez et al, 2006, Roldán & Ramírez, 2008García & Dister, 1990;Criales-Hernández & Jerez-Guerrero, 2016;Solís-Parra & Criales-Hernández, 2016). Conductivity values indicated high ionic and dissolved solids content, probably associated with river runoff and anthropogenic activities from agricultural and livestock farming activities in the area (Kalff, 2002;Peña et al, 2005;Gallo-Sánchez et al, 2009;Pinilla et al, 2010;Barón-Rodríguez et al, 2006;Silva et al, 2017).…”
Section: Physical and Chemical Variablessupporting
confidence: 85%
“…The pH and conductivity values recorded for the tropical lowland lakes in the study area were similar to those reported for other lowland lakes of the Middle Magdalena River, such as Ciénaga de Paredes, Ciénaga de Chucuri, Ciénaga de Aguas Negras, Ciénaga San Silvestre, Ciénaga del Opón, and Ciénaga Miramar (Pedraza et al, 1989;Ramírez & Viña, 1998;Pava et al, 2006;Barón-Rodríguez et al, 2006, Roldán & Ramírez, 2008García & Dister, 1990;Criales-Hernández & Jerez-Guerrero, 2016;Solís-Parra & Criales-Hernández, 2016). Conductivity values indicated high ionic and dissolved solids content, probably associated with river runoff and anthropogenic activities from agricultural and livestock farming activities in the area (Kalff, 2002;Peña et al, 2005;Gallo-Sánchez et al, 2009;Pinilla et al, 2010;Barón-Rodríguez et al, 2006;Silva et al, 2017).…”
Section: Physical and Chemical Variablessupporting
confidence: 85%